Effects of Foliar Application of Uniconazole on the Storage Quality of Tuberous Roots in Sweetpotato - Ximing Xu; Xueping Pan; Heyao Zhang; Zunfu Lv; Jiaping Xia; Peng Cheng; Melvin Sidikie George; Yu Chen; Linjiang Pang; Guoquan Lu (Agronomy, 2022)
Uniconazole (UCZ), as a plant growth regulator, has been extensively applied in sweetpotato (Ipomoea batatas (L.) Lam) to increase tuberous root yield and quality. It is usually used in the production of sweetpotato by foliar spray. The post-harvest storage stage is crucial for forming the quality of the sweetpotato’s tuberous root. Few studies have focused on the foliar spraying UCZ-affected storage quality of sweetpotato during pro-harvest storage. To examine the effects of foliar application of UCZ on the storage quality of tuberous root, this study mainly analyzed the influence of storage quality, with (K2 and K4) and without (K1 and K3) 100 mg·L−1 foliar spraying of UCZ, at a storage period of normal fertilizing treatments (K1 and K2) and rich fertilizing treatments (K3 and K4), on the storage quality of three representative sweetpotato varieties (Z13, Z33 and J26). Compared to the no-use UCZ treatments, the decay rate of K2 was the lowest for any storage time. The decay rate of all the varieties was 0.0% before 45 DAS. Only the decay rate of Z33 increased to 4.4% at 60 DAS (p < 0.05). The dry matter rate of K2 and K4 was still higher than that of K1 during 15–60 DAS in Z13 and J26 (p < 0.05). UCZ foliar spraying was higher than without treatment at 30–60 DAS. In Z33, the springiness of UCZ spraying was higher than no spraying treatments at 45–60 DAS. These results indicate that foliar spraying of UCZ had no effect on the storage quality of tuberous root decreasing sharply, and it sometimes kept the quality stable.